Feasibility and effectiveness of MATCH-ADTC on ninth-grade students presenting symptoms of depression, and anxiety - Holloway, Samantha Marie Kriley (Kansas State University, 2020)
Anxiety and depression symptoms in school-aged children are highly prevalent and can be comorbid. Mental health interventions are promising in decreasing anxiety and depression symptoms as well as learning healthy coping techniques. MATCH-ADTC is a transdiagnostic intervention grounded in cognitive-behavioral therapy and designed for children ages 6 to 15. The current study investigates the feasibility and effectiveness of MATCH-ADTC intervention on 15 ninth grade students that included both student self-reports and teacher reports. Students found MATCH-ADTC to be feasible (M = 1.89, SD = 0.34). Individual graphs of Internalizing Problem and Total Problem from the Brief Problem Monitor (BPM) found eight and seven student self-reports decreased over the course of MATCH-ADTC intervention, respectively. Individual graphs of Internalizing Problem and Total Problem from the Brief Problem Monitor (BPM) found five and ten teacher reports decreased over the course of MATCH-ADTC intervention, respectively. Results from the longitudinal multilevel modeling found an intercept range of 59.42 – 66.7. Intercepts below 65 indicate individuals did not have severe enough symptom of depression or anxiety as indicated by the Brief Problem Monitor. No statistically significant difference was found on the pre-and-post-test Beck Depression Inventory (t (14) = 0.68, p = 0.51) and Beck Anxiety Inventory (t(14) = 1.17, p = 0.26). The transdiagnostic intervention of MATCH-ADTC has provided evidence of potential for reduction in symptoms of anxiety and depression in school-aged children. However, more research should be completed on the effectiveness of MATCH-ADTC of school-aged children.
Keywords: Transdiagnostic; Anxiety; Depression; School counselor; MATCH-ADTC